Acute Schistosomiasis: A Risk Underestimated by Travelers and a Diagnosis Frequently Missed by General Practitioners—A Cluster Analysis of 42 Travelers. Issue 3 (21st January 2015) - Rochat, Laurence; Bizzini, Alain; Senn, Nicolas; Bochud, Pierre‐Yves; Genton, Blaise; de Vallière, Serge
Abstract : Background: In 2011, a patient was admitted to our hospital with acute schistosomiasis after having returned from Madagascar and having bathed at the Lily waterfalls. On the basis of this patient's indication, infection was suspected in 41 other subjects. This study investigated (1) the knowledge of the travelers about the risks of schistosomiasis and their related behavior to evaluate the appropriateness of prevention messages and (2) the diagnostic workup of symptomatic travelers by general practitioners to evaluate medical care of travelers with a history of freshwater exposure in tropical areas. Methods: A questionnaire was sent to the 42 travelers with potential exposure to schistosomiasis. It focused on pre‐travel knowledge of the disease, bathing conditions, clinical presentation, first suspected diagnosis, and treatment. Results: Of the 42 questionnaires, 40 (95%) were returned, among which 37 travelers (92%) reported an exposure to freshwater, and 18 (45%) were aware of the risk of schistosomiasis. Among these latter subjects, 16 (89%) still reported an exposure to freshwater. Serology was positive in 28 (78%) of 36 exposed subjects at least 3 months after exposure. Of the 28 infected travelers, 23 (82%) exhibited symptoms and 16 (70%) consulted their general practitioner before the information about the outbreak had spread, but none of these patients had a serology for schistosomiasis done during the first consultation. Conclusions: The usual prevention message of avoiding freshwater contact when traveling in tropical regions had no impact on the behavior of these travelers, who still went swimming at the Lily waterfalls. This prevention message should, therefore, be either modified or abandoned. The clinical presentation of acute schistosomiasis is often misleading. General practitioners should at least request an eosinophil count, when confronted with a returning traveler with fever. If eosinophilia is detected, it should prompt the search for a parasitic disease.